a PHILOSOPHICAL THOUGHTS OF NGUYEN TRUONG TO - Chinh, Doan (Perkumpulan Dosen Program Hibah Indonesia, 2023)
Nguyen Truong To is one of the figures who advocated a fairly comprehensive reform policy in the fields of politics, economy, military, diplomacy, academia, education, culture and society modern times in Vietnam. Behind those hearings are philosophical views, which serve as the theoretical basis for his innovative thought, expressed in terms of world outlook, epistemology, outlook on life, morals and social and political life.